Determining oneself as an Argentine writer: the “Ghostly” Language of Alan Pauls - Rodríguez Montiel, Emiliano (2023)
This paper focuses on Alan Pauls' literary beginnings, specifically on his first two novels: El pudor del pornógrafo (1984) and El coloquio (1990). Through the analysis of the European and extemporaneous system of correspondences (Kafka, Klossowski, Goethe, Bataille) that intervenes in the creative process of these texts, our argumentation aims to evidence, firstly, the immediate context with which this narrative decides, from its beginnings, to antagonize: those writings related to the idea of a literary work linked to politicization, memorialism, pedagogical function, folklorism. And, secondly, closely linked to the above: the set of choices (thematic, theoretical, filiatory, formal and evaluative) that Pauls takes to make a place for himself in his national tradition. An Argentine condition of writer, that is, universal, whose formal translation, such is our hypothesis, is the composition of an “aphantasmed” language: a language carved from within by other languages, capable of exiling the writer from his own time in order to invent his own contemporaneity.